Case report: Takotsubo syndrome induced by severe hypoglycemia - Xia, Panpan; Zhang, Yan; Sun, Yumin; Wang, Jun (Frontiers in Cardiovascular Medicine, 2022)
Background: Takotsubo syndrome (TTS) is a disorder frequently characterised by transient dysfunction of the apical portion of the left ventricle with hyperkinesis in other parts of the heart walls. TTS is also called stress cardiomyopathy because it is known to be triggered by emotional or physical stress. We report a case of TTS associated with severe hypoglycaemia. Case summary: An 85-year-old female patient with a history of non-insulin-dependent diabetes mellitus and hypertension presented to the emergency department with hypoglycaemia-induced unconsciousness. The patient regained consciousness after an intravenous glucose injection. The patient complained of chest discomfort after the correction of hypoglycaemia. Electrocardiography revealed ST-segment elevation in leads V2-V5, therefore, ST-segment elevation myocardial infarction was highly suspected. Echocardiography showed impaired left ventricular systolic function with an ejection fraction of 40% accompanied by hypokinesis of the apex. Percutaneous coronary angiography showed 30% stenosis of the left anterior descending coronary artery. Left ventricular angiography revealed apical dyskinesia, which is typical of the classic apical ballooning shape of takotsubo. The patient was diagnosed with TTS and managed with pharmacological therapy, including antiplatelet (i.e., aspirin), lipid-lowering, anti-heart failure, and hypoglycaemic drugs. The patient was successfully discharged in a stable condition. Conclusion: This is a representative case of TTS caused by hypoglycaemia. Due to the self-limiting nature of TTS, diagnoses can be missed among hypoglycaemic patients. Thus, echocardiography is required for patients with hypoglycaemia to ensure an accurate TTS diagnosis in the emergency department.